Standardization of a Chemical Modification Protocol for Jute Fabric Reinforcement - L. Ammayappan; S. Chakraborty; I. Musthafa; N.C. Pan (Journal of Natural Fibers, 2022)
Surface modification of a jute fibrous reinforcement is preferred to improve its compatibility with thermosetting resin for the development of biocomposite. A plain weave jute fabric was chemically modified with different concentrations of sodium hydroxide (NaOH) i.e. 1 to 6% (weight/volume). The chemically modified jute fabrics were assessed for their physical, mechanical, and morphological properties. The modified jute reinforcements were used for the preparation of biocomposite by hand laying method cum compression molding method, and the respective biocomposites were evaluated for their physical and mechanical properties. Results inferred that NaOH modified the fine structure and morphological properties of treatment on jute reinforcement and the reinforcing ability of the modified jute fabric is increased with increasing in the concentration of NaOH up to 5% (w/v) and then stabilized. It is concluded that the suitable concentration for improved reinforcement is found at 5% (w/v) at 30°C for 60 min in 1:15 material-to-liquor ratio.